Regex with ChatGPT - Taulli, Tom 1968- (O'Reilly Media, Inc., 2024)
Whether you're a developer, a creative writer, or business manager, these shortcuts will help you get the most from ChatGPT. Topics include generating content and artwork, developing software code, and building custom GPTs. Each video contains practical tips to help you leverage ChatGPT.
Online resource; title from title details screen (O'Reilly, viewed June 18, 2024)
Keywords: ChatGPT; Regular expressions (Computer science); Natural language processing (Computer science); Artificial intelligence -- Computer programs; Expressions rationnelles (Informatique); Traitement automatique des langues naturelles; Intelligence artificielle; Logiciels; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet